KILchip v1.0: a novel plasmodium falciparum merozoite protein microarray to facilitate malaria vaccine candidate prioritization - Kamuyu, Gathoni; Tuju, James; Kimathi, Rinter; Mwai, Kennedy; Mburu, James; Kibinge, Nelson; Chong Kwan, Marisa; Hawkings, Sam; Yaa, Reuben; Chepsat, Emily; Njunge, James M.; Chege, Timothy; et al. (Frontiers in immunology, 2018)
Passive transfer studies in humans clearly demonstrated the protective role of IgG antibodies against malaria. Identifying the precise parasite antigens that mediate immunity is essential for vaccine design, but has proved difficult. Completion of the Plasmodium falciparum genome revealed thousands of potential vaccine candidates, but a significant bottleneck remains in their validation and prioritization for further evaluation in clinical trials. Focusing initially on the Plasmodium falciparum merozoite proteome, we used peer-reviewed publications, multiple proteomic and bioinformatic approaches, to select and prioritize potential immune targets. We expressed 109 P. falciparum recombinant proteins, the majority of which were obtained using a mammalian expression system that has been shown to produce biologically functional extracellular proteins, and used them to create KILchip v1.0: a novel protein microarray to facilitate high throughput multiplexed antibody detection from individual samples. The microarray assay was highly specific; antibodies against P. falciparum proteins were detected exclusively in sera from malaria-exposed but not malaria-naïve individuals. The intensity of antibody reactivity varied as expected from strong to weak across well-studied antigens such as AMA1 and RH5 (Kruskal-Wallis H test for trend: p-value <0.0001). The inter-assay and intra-assay variability was minimal, with reproducible results obtained in re-assays using the same chip over duration of 3 months. Antibodies quantified using the multiplexed format in KILchip v1.0 were highly correlated with those measured in the gold-standard monoplex ELISA (median (range) Spearman’s R of 0.84 (0.65-0.95)). KILchip v1.0 is a robust, scalable and adaptable protein microarray that has broad applicability to studies of naturally acquired immunity against malaria by providing a standardized tool for the detection of antibody correlates of protection. It will facilitate rapid high-throughput validation and prioritization of potential Plasmodium falciparum merozoite-stage antigens paving the way for urgently needed clinical trials for the next-generation of malaria vaccines.